Implementing universal design in a Norwegian context: Balancing core values and practical priorities - Lid, Inger Marie (Disability Studies Quarterly, 2016)
How can urban planning processes include perspectives from people with disabilities? This paper discusses the implementation of universal design (UD) and accessibility in a local urban context. Universal design consists of both core values, such as inclusion and equal status, and specific design initiatives, such as design of pavement surfaces and benches. The aim of implementing universal designing strategies is to achieve equal access for all citizens. The paper interprets the urbanist Henri Lefebvre's notion of the right to the city as a right to participate in urban life and thus a dimension of equal citizenship on a very concrete level. The right to participate in urban life is closely linked to access to the built environment. Based on an empirical study of an urban redesign project, I argue that equal access must imply both access to public places and to political processes.